Coloured Muṣḥaf and Young Ḥāfiẓa: Exploring the Reception of Tailored Muṣḥafs for Memorisation among Taḥfīẓ Circles in Indonesia - Wardatun Nadhiroh; Supriansyah (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2024)
The practice of Qur’an memorisation, or taḥfīẓ, holds deep spiritual and educational significance in Islamic tradition. In Indonesia, the introduction of tailored muṣḥafs, specialised Qur’anic editions featuring colour-coded tajwīd rules, progress trackers, and other mnemonic aids, has transformed the landscape of taḥfīẓ practices. Drawing on the framework of Qur’anic reception, this study explores how these muṣḥafs are received among taḥfīẓ circles from both institutional and individual perspectives. Based on qualitative fieldwork in taḥfīẓ institutions, the research reveals that while institutions value tailored muṣḥafs for their ability to standardise and streamline the memorisation process, individual memorisers appreciate their personalised features, which encourage autonomy and spiritual engagement. These muṣḥafs are particularly celebrated for their inclusivity, making Qur’an memorisation accessible to diverse demographics beyond formal settings. This study contributes to current discussions on contemporary Qur’anic engagement by showing how material design shapes both the pedagogy and lived experience of taḥfīẓ. However, challenges such as the commodification of religious texts and potential over-reliance on visual aids raise concerns about preserving the oral and spiritual essence of the taḥfīẓ tradition. The findings underscore the dual role of tailored muṣḥafs in modernising the taḥfīẓ practice while highlighting the need for a balanced approach to sustain its sacred and cultural heritage.